How an egg grows into a chicken - Kant, Tanya (Amaze (Children's Press (New York, N.Y.)), 2009)
Why do chickens lay eggs? Why do they sit on them? And why doesn't the egg break when the hen sits on it? Follow the amazing life cycle of a chicken from egg to adult.